Highlights of the Customs Union - Alexander Vladimirovich Kharlov; Dmitry Yurievich Nozhenko (Экономика региона, 2012)
The authors summarize the main results of two years of the operation of the Customs Union in Belarus, Kazakhstan and Russia, which is hardly impressive in the aftermath of the global financial crisis and economic instability in Belarus. However, the authors stressed that it is too early to jump to conclusions about the effectiveness of the Customs Union. In addition, the structure of trade, working arrangements and the list of goods are changed. Separately it is analyzed the changing economic situation in Kazakhstan, where the increased influx of Russian investments are after joining the Customs Union fully operational. In different sectors of the domestic economy are active joint Kazakh-Russian companies because Kazakhstan has more attractive business environment, compared to Russia. Russian companies are interested in Kazakhstan and produce this product to sell back to Russia or Belarus. For Kazakhstan benefit is job creation, expansion of production base, increasing tax revenues, new investments.